Carnoy's solution in the mangement of odontogenic keratocyst - Sivaraj Sivanmalai; Kohila Kandhasamy; Neetika Prabu; Christo Naveen Prince; Chandrakala Shekarappa Annapurna Pannaikadu Somasundaram Prabu (Wolters Kluwer Medknow Publications, 2012)
Carnoy's solution is a substance used as a complementary treatment after the conservative excision of odontogenic keratocyst. The application of Carnoy's solution promotes a superficial chemical necrosis and is intended to reduce recurrence rates. However, the inferior alveolar vascular-nervous plexus can occasionally be exposed after the removal of a lesion. The safety of the application of Carnoy's solution over this plexus has been reported, but to date, no clinical report has been made. The authors present a case that was given Carnoy's solution over the inferior alveolar vascular-nervous plexus as a complementary treatment for the keratocystic odontogenic tumor. Effective control of recurrence with low and transient neural morbidity was suggested with this technique.